2019
DOI: 10.1016/j.mimet.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex real-time PCR assay for the detection and differentiation of five bovine pinkeye pathogens

Abstract: A B S T R A C TInfectious bovine keratoconjunctivitis (IBK), also known as pinkeye, is one of the most common eye diseases in cattle. Several pathogens have been associated with IBK cases, however, Moraxella bovis, Moraxella bovoculi, Mycoplasma bovis, Mycoplasma bovoculi and bovine herpesvirus type 1 (BHV-1) are most frequently observed. A multiplex real-time PCR assay using two reactions was developed for the detection and differentiation of these five pathogens. Detection sensitivities of the multiplex assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…and Moraxella spp. to be the major pathogens that predispose cattle to IBK [ 1 , 8 , 9 ]. The mean abundance of these taxa in the current dataset is shown in Figure S5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Moraxella spp. to be the major pathogens that predispose cattle to IBK [ 1 , 8 , 9 ]. The mean abundance of these taxa in the current dataset is shown in Figure S5 .…”
Section: Resultsmentioning
confidence: 99%
“…Although many factors contribute to an IBK infection, Moraxella bovis is typically the principal etiologic agent of IBK [ 7 ]. Other agents such as Moraxella bovoculi and Mycoplasma bovoculi have also been associated with IBK outbreaks and their presence may predispose the animal to disease [ 1 , 8 , 9 ]. It is suggested that Moraxella and Mycoplasma enter the eye via face flies or as an effect of secretion after irritation of the eye due to cuts from tall grass, feed, or UV light damage from the sun [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most notable and frequently isolated of these associated bacteria is Moraxella bovoculi (Angelos et al, 2007b). While M. bovoculi has been unsuccessful at inducing IBK experimentally (Gould et al, 2013), it is more frequently isolated from IBK lesions when compared to M. bovis, using both aerobic culture and molecular detection techniques (Loy and Brodersen, 2014;Zheng et al, 2019). Despite the lack of proven causation for M. bovoculi in IBK to date, in 2017 the USDA approved the first conditionally licensed M. bovoculi based vaccine product to be marketed for the prevention of IBK (USDA CVM code: 2A77.00, Addison Biological Laboratory).…”
Section: Introductionmentioning
confidence: 99%
“…There are several pathogens were incriminated as etiologic agent responsible for IKC. However, Moraxella with and/or without other pathogens was implicated as a major pathogen causes IKC in small and large ruminants (Abdullah et al, 2015;Gelormini, et al, 2017 andZheng et al, 2019). Moreover, frequent isolation of different microorganisms from ruminants with signs of IKC may attributed to the synergistic action between environmental risk factors and opportunistic pathogens habitat eye (Sağlam etal., 2018).…”
Section: Introductionmentioning
confidence: 99%